Inorganic Carbon Accumulation and Photosynthesis in a Blue-green Alga as a Function of External pH - Coleman, John R. (1981)
The blue-green alga Coccochloris peniocystis photosynthesizes optimally over the pH range of 7.0 to 10.0, but the O(2)-evolution rate is inhibited below pH 7.0 and ceases below pH 5.25. Measurement of the inorganic carbon pool in this alga in the light, using the silicone-fluid filtration technique demonstrated that the rate of accumulation of dissolved inorganic carbon remained relatively constant over a wide pH range. At external dissolved inorganic carbon concentrations of 0.56 to 0.89 millimolar the internal concentration after 30 seconds illumination was greater than 3.5 millimolar over the entire pH range. Intracellular pH measured in the light using [(14)C]5,5-dimethyloxazolidine-2,4-dione and [(14)C]methylamine dropped from pH 7.6 at an external pH of 7.0 to pH 6.6 at an external pH of 5.25. Above an external pH of 7.0 the intracellular pH rose gradually to pH 7.9 at an external pH 10.0. Ribulose-1,5-bisphosphate carboxylase activity of cell-free algal extracts exhibited optimal activity at pH 7.5 to 7.8 but was inactive below pH 6.5. It is suggested that the inability of Coccochloris to maintain its intracellular pH when in an acidic environment restricts its photosynthetic capacity by a direct pH effect on the principal CO(2) fixing enzyme.